THE ABILITY OF THE CORPORATE GOVERNANCE PERCEPTION INDEX (CCGPI) TO MODERATE THE RELATIONSHIP BETWEEN PROFIT PERSISTENCE, GREEN INTELLECTUAL CAPITAL AND PROFIT GROWTH WITH PROFIT QUALITY - Widarnaka; Suripto; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to test the ability of the Corporate Governance Perception Index (CGPI) in moderating the influence of profit persistence, green intellectual capital, and profit growth on profit quality. This study uses quantitative data obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) as well as CGPI reports for the 2018-2022 period. The results of the study show that the persistence of profit and green human capital have a significant effect on the quality of profit. Meanwhile, green structural capital and green relational capital also have a positive, but not significant, influence. The Corporate Governance Perception Index (CGPI) has been proven to moderate the influence of green human capital and profit growth on profit quality. This study concludes that the implementation of good corporate governance can improve the quality of company profits.